493 Prognostic value of myocardial scar and chamber enlargement at electroanatomical mapping during catheter ablation in adult congenital heart disease. (8th December 2021) - Perna, Francesco; Narducci, Maria Lucia; Sabarese, Rocco; Ruscio, Eleonora; Scacciavillani, Roberto; Spera, Francesco Raffaele; Gianluigi, Bencardino; Pinnacchio, Gaetano; Pelargonio, Gemma; Crea, Filippo
Abstract: Aims: Atrial and ventricular tachyarrhythmias are common among patients with adult congenital heart disease (ACHD) and can impair quality of life and prognosis. Catheter ablation is often the main treatment option in this population, despite anatomical hurdles. Substrate mapping findings have not been thoroughly investigated as predictors of arrhythmia recurrence success and cardiovascular clinical outcome after ablation. We sought to determine the prognostic value of myocardial scar and chamber enlargement detected at electroanatomical mapping in ACHD patients undergoing catheter ablation of tachyarrhythmias. Methods and results: Consecutive ACHD patients undergoing catheter ablation of atrial and ventricular tachycardias using different electroanatomical mapping systems were retrospectively identified from a hospital-based database. Scar extent detected at the electroanatomical mapping, as well as the total mapped area, was calculated. Arrhythmia recurrence, hospitalization for cardiovascular (CV) reasons, and a combined endpoint (arrhythmia recurrence and/or CV hospitalization) were evaluated during the follow-up. The relationship between the aforementioned electroanatomical findings and the patients' outcome was assessed. Twenty patients (12 male, 60%; mean age 40 ± 11 years) undergoing atrial ( n  = 14; 70%) or ventricular ( n  = 6; 30%) tachyarrhythmia were included. Acute procedural success (arrhythmia termination and/or no reinduction) was achieved in all the patients. At a mean follow-up of 171 ± 135 weeks, eight patients (40%) had arrhythmia recurrence (4/6 in the ventricular tachycardia group, 67%, 4/14 in the atrial tachycardia group, 28%). Patients with arrhythmia recurrence had a more extensive bipolar scar ( P  = 0.029) and a larger total mapped area ( P  = 0.03) than patients without recurrence, and so did the patients with the composite endpoint ( P  = 0.029 and P  = 0.03, respectively). Patients with subsequent CV hospitalization had a larger total mapped area than patients without CV hospitalization ( P  = 0.017). The presence of a bipolar scar ≥22.95 cm 2 predicted arrhythmia relapse (0.039) at the multivariate analysis. Conclusions: Patients with ACHD show a high recurrence rate after catheter ablation, especially for ventricular tachycardias. A large bipolar scar at the electroanatomical mapping and total mapped area predict arrhythmia recurrence, likely due to the presence of more extensive reentry circuits. A large total mapped area, which may reflect a greater disease severity, predicts both arrhythmia recurrence and CV hospitalizations. Early referral of ACHD patients for catheter ablation may be a sound strategy in order to perform the procedure in the setting of less advanced heart disease.